N-Methyl-D-Aspartate Receptors Involvement in the Gentamicin-Induced Hearing Loss and Pathological Changes of Ribbon Synapse in the Mouse Cochlear Inner Hair Cells - Juan Hong; Yan Chen; Yanping Zhang; Jieying Li; Liujie Ren; Lin Yang; Lusen Shi; Ao Li; Tianyu Zhang; Huawei Li; Peidong Dai (Neural Plasticity)
Cochlear inner hair cell (IHC) ribbon synapses play an important role in sound encoding and neurotransmitter release. Previous reports show that both noise and aminoglycoside exposures lead to reduced numbers and morphologic changes of synaptic ribbons. In this work, we determined the distribution of N-methyl-D-aspartate receptors (NMDARs) and their role in the gentamicin-induced pathological changes of cochlear IHC ribbon synaptic elements. In normal mature mouse cochleae, the majority of NMDARs were distributed on the modiolar side of IHCs and close to the IHC nuclei region, while most of synaptic ribbons and α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR) were located on neural terminals closer to the IHC basal poles. After gentamicin exposure, the NMDARs increased and moved towards the IHC basal poles. At the same time, synaptic ribbons and AMPARs moved toward the IHC bundle poles on the afferent dendrites. The number of ribbon synapse decreased, and this was accompanied by increased auditory brainstem response thresholds and reduced wave I amplitudes. NMDAR antagonist MK801 treatment reduced the gentamicin-induced hearing loss and the pathological changes of IHC ribbon synapse, suggesting that NMDARs were involved in gentamicin-induced ototoxicity by regulating the number and distribution of IHC ribbon synapses.